Fourth of July - McDonnell, Janet, 1962-; Endres, Helen (Chicago : Childrens Press, 1994)
Nina and her poodle Sammy experience the sights and sounds of a Fourth of July celebration. Includes crafts and tips on fireworks safety.
2.3
K-3
Keywords: Dogs -- Fiction; Fourth of July -- Fiction; Dogs -- Fiction; Fourth of July -- Fiction; Holidays -- Fiction